2012
DOI: 10.1016/j.brainres.2012.05.006
|View full text |Cite
|
Sign up to set email alerts
|

Connectivity graph analysis of the auditory resting state network in tinnitus

Abstract: Thirteen chronic tinnitus patients and fifteen age-matched healthy controls were studied on a 3 T magnetic resonance imaging (MRI) scanner during resting condition (i.e. eyes closed, no task performance). The auditory resting-state component was selected using an automatic component selection approach. Functional connectivity (correlations/anticorrelations) in the extracted network was portrayed by integrating the independent component analysis (ICA) approach with a graph theory method. Tinnitus and control gr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

17
123
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 173 publications
(140 citation statements)
references
References 52 publications
17
123
0
Order By: Relevance
“…More recent research provides more direct evidence for the neural-circuit hypothesis. Volumetric imaging research has shown that tinnitus patients had structural alterations both in the central auditory and in the limbic system [10,13,26], and functional network studies in tinnitus patients also revealed the enhanced coupling of auditory network and limbic systems [27][28][29]. These findings support the hypotheses that the limbic system plays a role in the generation of tinnitus, and tinnitus can stress and change neuronal activity and plasticity in the limbic system.…”
Section: Discussionsupporting
confidence: 62%
“…More recent research provides more direct evidence for the neural-circuit hypothesis. Volumetric imaging research has shown that tinnitus patients had structural alterations both in the central auditory and in the limbic system [10,13,26], and functional network studies in tinnitus patients also revealed the enhanced coupling of auditory network and limbic systems [27][28][29]. These findings support the hypotheses that the limbic system plays a role in the generation of tinnitus, and tinnitus can stress and change neuronal activity and plasticity in the limbic system.…”
Section: Discussionsupporting
confidence: 62%
“…This is reminiscent of what has been demonstrated in auditory cortex stimulation via implanted electrodes. The success of stimulation also depends on the presence of good functional connectivity between the auditory cortex (where the electrode was placed) and the parahippocampal gyrus, 9 which has been considered a critical hub in the tinnitus network, as it is involved in tinnitus in general 27,42,57 and in tinnitus lateralization more specifically, 47 as well as in tinnitus distress 37,46 and tinnitus-related depression. 21 Whereas these are only case reports, our results suggest that it is worthwhile to further explore this avenue of neuromodulation for tinnitus in severely distressed patients and that a biomarker consisting of EEG functional connectivity and/or rTMS might become important in selecting the right patient for this technique.…”
Section: Discussionmentioning
confidence: 99%
“…All episodic artifacts were removed from the stream of the EEG. Average Fourier cross-spectral matrices were computed for bands delta (2-3.5 Hz), theta (4-7.5 Hz), alpha (8-12 Hz), beta (13)(14)(15)(16)(17)(18)(19)(20)(21)(22)(23)(24)(25)(26)(27)(28)(29)(30), and gamma (30.5-45 Hz).…”
Section: Connectivity Changes Between Cases 1 Andmentioning
confidence: 99%
See 1 more Smart Citation
“…ICA with 30 components yielded statistically independent RSNs and possible artifacts (Hyvarinen et al, 2001;McKeown et al, 1998). Independent components corresponding to the DMN were selected using a previously published automated selection technique (Maudoux et al, 2012;Soddu et al, 2012). For this technique, using an average DMN template calculated on the basis of resting state fMRI scans from 12 healthy subjects [4 women, 8 men; mean age 21 years; standard deviation: 3 years ], who were scanned for a previous study on a 3T Siemens Allegra scanner (10 min resting state with eyes closed), we defined 14 ROIs (10 · 10 · 10 mm) that were considered to be most representative of the DMN based on previous research (Fair et al, 2008;Fox et al, 2005) (Supplementary Material S1; Supplementary Data are available online at www.liebertpub.com/brain).…”
Section: Ica-based Analysismentioning
confidence: 99%